Francesca Caccini's Il primo libro delle musiche of 1618 : a modern critical edition of the secular monodies - Caccini, Francesca, 1587-approximately 1640 (Indiana University Press, 2004)
Francesca Caccini (1587--ca. 1640) was an accomplished composer, singer, and instrumentalist in the tradition of the Florentine Camerata. Her 1618 volume Il primo libro delle musiche was dedicated to her patron the Cardinal de' Medici (1596--1666). This modern critical edition presents 17 secular monodies for one and two voices with figured bass accompaniment from this landmark collection. The book includes text translations, biographical and stylistic essays, recommendations on performance practi.